2019
DOI: 10.2478/sjecr-2019-0048
|View full text |Cite
|
Sign up to set email alerts
|

Complicated Root Canal Morphology of Permanent Mandibular Lateral Incisors is Associated with the Presence of a Second Mesiobuccal Canal in Permanent Maxillary First Molars

Abstract: Many studies have been conducted in order to define the root canal morphology based on age, gender, ethnic and racial characteristics of the population. However, relations within morphological variations of certain groups of teeth have rarely been investigated. The aim of this study was to evaluate the root canal morphology of mandibular lateral incisors and to determine the association between their morphologic characteristics and the presence of a second mesiobuccal canal of maxillary first molars. Cone-beam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Nevertheless, the etiology of this relationship remains unknown. Papic et al revealed the relevance of the MB2 canal of the maxillary first molar and two canals in mandibular lateral incisors [ 20 ]. They assumed that this could be related to the timing of root formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the etiology of this relationship remains unknown. Papic et al revealed the relevance of the MB2 canal of the maxillary first molar and two canals in mandibular lateral incisors [ 20 ]. They assumed that this could be related to the timing of root formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, no studies have been conducted on the relationship between DLR in the mandibular first molar and two canals in both mandibular central and lateral incisors simultaneously in the same subjects. The etiology of this relationship is still unclear, but Papic et al assumed that it would be related to the timing of root formation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%